Tracing Mathematical Function of Age Specific Fertility Rate in Peninsular Malaysia - Norsyela Muhammad Noor Mathivanan; Puzziawati Ab Ghani; Nor Azura Md.Ghani (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The size, structure, and composition of a population are affected by the fertility rates at any point of time. Many researchers took the opportunity to exploit the fertility rates in obtaining better fertility patterns for their country. The curve for the age specific fertility rate is consistent, and this feature allows the curve to be matched with a mathematical model. This paper aimed to identify the best mathematical model that fits the recent age specific fertility rate in Peninsular Malaysia. This study fitted the fertility data of Peninsular Malaysia from 1996 to 2014 to the four mathematical models, which were Hadwiger, Gamma, Beta, and Gompertz models. From the comparisons of the four models, it was found that the best fitted mathematical model is Hadwiger model. In relation to the data of early 21st century, there was an inclination for the best fitted mathematical model from Hadwiger model to Beta model. Hence, the best mathematical model for each year can be used to convert a fertility schedule classified in a five-year age group into a fertility schedule for a single-year of age in Peninsular Malaysia. This model also can be helpful for population projections by using limited and defective data.